Synthesis of nanocomposite materials with montmorillonite and multiwalled carbon nanotubes - Mandakhsaikhan, Luvsandagva; Anudari, Dolgormaa; Altantuya, Ochirkhuyag; Oyun-Erdene, Gendenjamts (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
The purpose of this study was to produce a nanocomposite material by modifying and combining natural montmorillonite clay from the Khumuult deposit with multi-walled carbon nanotubes. Clay and multi-walled carbon nanotubes were pre-treated separately in several steps before combining them to produce a composite material. Mechanical processing was used to enrich the mineral montmorillonite from natural clay samples. The enriched montmorillonite sample was then autoclaved in alkali (NaOH), and the amount of total silica in the clay sample decreased from 38.4% to 21.7% in X-ray fluorescence analysis, indicating that the alkali treatment was effective. After functionalization, Fourier transform infrared spectroscopy (FTIR) spectroscopic analysis revealed the intensity of the amine group at 1540 and 2356 cm-1 , proving that the amine group successfully interacted on the montmorillonite. Commercial multiwalled carbon nanotubes were oxidized and carboxylated to increase activity and yield a composite. The FTIR, X-ray diffractometer, Scanning Electron Microscope (SEM), and Raman spectroscopy were used to investigate the properties of composite materials. According to the test results, the chemical composition of the composite material was 19.65% carbon, 41.06% oxygen, 8.86% aluminum, 9.75% silicon, and 7.52% iron. SEM analysis of our synthesized composite material revealed that multi-walled carbon nanotubes were evenly distributed on the surface of the clay. Further, it is considered necessary to conduct a detailed study of the characteristics and applications of the composite materials synthesized. Монтмориллонит ба олон ханат нүүрстөрөгчийн нано хоолой бүхий нано композит материалын нийлэгжүүлэлт Хураангуй: Хөмүүлтийн ордын монтмориллонитын төрлийн байгалийн шаврыг олон ханат нүүрстөрөгчийн нано хоолойтой нийлэгжүүлж, нано композит материал гарган авах зорилгоор энэхүү судалгааны ажлыг гүйцэтгэлээ. Байгалийн шаврын дээжинд механик боловсруулалт хийж монтмориллонитыг баяжуулсан. Баяжуулсан дээжинд автоклавын аргаар шүлтийн боловсруулалт хийж үр дүнг рентгенфлуоросценцын аргаар тодорхойлоход, шаврын дээж дэх нийт цахиурын оксидийн хэмжээ 38.4%-иас 21.7% болж буурсан нь шүлтийн боловсруулалт үр дүнтэй явагдсаныг харуулж байна. Шүлтийн боловсруулалт хийсэн шаврыг гексаметилэндиаминаар үйлчлэн амин (-NH2) бүлгийг суулгасан бөгөөд нил улаан туяаны спектроскопын шинжилгээгээр амин бүлгийн эрчим илэрсэн. Худалдааны олон ханат нүүрстөрөгчийн нано хоолойг исэлдүүлэн, карбоксилжүүлж бэлтгэсэн. Шавар болон олон ханат нүүрстөрөгчийн нано хоолойг тус тусад нь боловсруулалт хийсний эцэст композит материалыг химийн аргаар нийлэгжүүлэн гарган авсан. Композит материалын шинж чанарыг судлахдаа нил улаан туяаны спектрометр, рентгендифрактометр, сканнинг электрон микроскоп болон раман спектроскопын шинжилгээний аргыг ашигласан. Туршилтын дүнгээс харахад, композит материал нь химийн найрлагын хувьд нүүрстөрөгч 19.65%, хүчилтөрөгч 41.06%, хөнгөнцагаан 8.86%, цахиур 9.75%, төмөр 7.52% агуулгатай байсан ба шаврын гадаргуу дээр олон ханат нүүрстөрөгчийн нано хоолой жигд тархан сууж, композит материал нийлэгжсэн болох нь сканнинг электрон микроскопын шинжилгээний дүнгээс харагдаж байв. Цаашид гарган авсан композит материалын шинж чанарын болон хэрэглээний судалгааг нарийвчлан хийх шаардлагатай гэж үзэж байна. Түлхүүр үг: шавар, механик боловсруулалт, шүлтийн боловсруулалт, автоклав.